(untitled) (International Journal of Nursing Education, 2021)
Background: Anxiety is considered as a widespread phenomenon that constitutes a worldwide reasonof reduced academic achievements among students. Aim:To investigate the relationship between studentnurse’s anxiety from exams and their quality of life in selected universities at KSA. Subject and Methods:A descriptive cross-sectional research design on 189 student nurses from HafrAl Batin university.One toolis divided into three main parts; demographic data, and student’s anxiety levels during exams, and student’squality of life assessment sheets. Results: there are a statistically significant correlation between student’sanxiety during exams and their quality of life ((p <0.001). Conclusion & Recommendations: there arestatistically significant relations were found between student’s anxiety during exams and quality of life withtheir sociodemographic characteristics in item only related to the barrier faced in life for adaptation andcompliance with exams. From the foregoing conclusion, students must receive regular; periodic in-servicepsychological rehabilitative program contains methods of adaptation and compliance with exams whichindirectly promote their quality of life.